LiDAR relocalization on edge devices - Lim, Christopher Jia Yao (Nanyang Technological University, 2021)
Simultaneous localization and mapping (SLAM), with the aid of cheap cameras, has many applications today. In niche situations where cameras are inappropriate, such as for privacy or security reasons, LiDARs have stepped up to fill the gap. However, much of the literature studying LiDAR SLAM have focused on autonomous vehicles with powerful spindle-type LiDAR sensors. There is a potential for LiDAR SLAM to be incorporated into many other areas such as home electronics, mobile devices, and even wearable technology. This paper explores the possibility of extending LiDAR relocalization methods to edge devices, by assuming edge devices do not have access to powerful LiDAR sensors, and also have limited processing capabilities.